The Molecular Basis of Kale Domestication: Transcriptional Profiling of Developing Leaves Provides New Insights Into the Evolution of a Brassica oleracea Vegetative Morphotype - Arias, Tatiana; Niederhuth, Chad E.; McSteen, Paula; Pires, J. Chris (Frontiers in Plant Science, 2021)
Morphotypes of Brassica oleracea are the result of a dynamic interaction between genes that regulate the transition between vegetative and reproductive stages and those that regulate leaf morphology and plant architecture. In kales, ornate leaves, extended vegetative phase, and nutritional quality are some of the characters potentially selected by humans during domestication. We used a combination of developmental studies and transcriptomics to understand the vegetative domestication syndrome of kale. To identify candidate genes that are responsible for the evolution of domestic kale, we searched for transcriptome-wide differences among three vegetative B. oleracea morphotypes. RNAseq experiments were used to understand the global pattern of expressed genes during a mixture of stages at one time in kale, cabbage and the rapid cycling kale line TO1000. We identified gene expression patterns that differ among morphotypes, and estimate the contribution of morphotype-specific gene expression that sets kale apart (3958 differentially expressed genes). Differentially expressed genes that regulate the vegetative to reproductive transition were abundant in all morphotypes. Genes involved in leaf morphology, plant architecture, defense and nutrition were differentially expressed in kale. This allowed us to identify a set of candidate genes we suggest may be important in the kale domestication syndrome. Understanding candidate genes responsible for kale domestication is of importance to ultimately improve Cole crop production.